2016
DOI: 10.15639/teflinjournal.v27i1/1-22
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motivational Strategies of Successful Teachers

Abstract: This multiple case study investigated how teachers implemented motivational teaching strategies and the impact of these strategies on students' motivation in an Indonesian high school context. The participants were four teachers and four groups of their students. The data were collected from teachers by conducting semi-structured interviews, classroom observations, and stimulated recall, and from the students through focus group interviews. The findings of the research indicated that each teacher had unique st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
4
24
0
2
Order By: Relevance
“…Previous studies have been conducted to shed light on the need of facilitating technology more into our practice as teacher. (Astuti, 2016;Blattner & Fiori, 2009;Grewal & Harris, 2009;Guikema & Williams, 2014;Guikema & Menke, 2014;Hattem, 2014;Kalasi, 2014;Lomicka & Lord, 2012Yunus et.al, 2012) Thus, choosing the most suitable social media application will be subject to classroom teacher's judgment.…”
Section: Instagrammingmentioning
confidence: 99%
“…Previous studies have been conducted to shed light on the need of facilitating technology more into our practice as teacher. (Astuti, 2016;Blattner & Fiori, 2009;Grewal & Harris, 2009;Guikema & Williams, 2014;Guikema & Menke, 2014;Hattem, 2014;Kalasi, 2014;Lomicka & Lord, 2012Yunus et.al, 2012) Thus, choosing the most suitable social media application will be subject to classroom teacher's judgment.…”
Section: Instagrammingmentioning
confidence: 99%
“…Many studies on teachers motivational strategies concur that the key basic to motivational context is the teacher's personality, particularly his or her willingness to be open and share his or her life with students (Nichols, 2014). Besides, Astuti (2016) researched on similar topic. The finding showed that the most influential teachers' motivational strategy was EFL classroom teacher's behaviour.…”
Section: B Maintaining Teachers' Motivational Strategiesmentioning
confidence: 99%
“…The finding showed that the most influential teachers' motivational strategy was EFL classroom teacher's behaviour. The teacher's behaviour which motivated students reported by Astuti (2016) could be seen from the teacher's smile, facial expression, jokes, and clear instruction in delivering lesson.…”
Section: B Maintaining Teachers' Motivational Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, supportive learning atmosphere is proved to be able to create successful learners since they become more motivated during their classroom learning process (Astuti, 2016). They are not anymore keeping silent in their classroom speaking practices.…”
Section: The Third Important Point Is That Through Text Based Speakinmentioning
confidence: 99%